Proton exchange reactions in isotope chemistry (II) synthesis of stable isotope‐labeled LCQ908. (14th October 2014) - Jian, Zhigang; Ray, Tapan; Wu, Amy; Jones, Lawrence; Forseth, Ry
<x xml:space="preserve">Abstract</x> The proton exchange reaction was applied to the preparation of stable isotope‐labeled LCQ908. For this synthesis, a suitable intermediate with protons alpha to a carbonyl group was first subjected to the H–D exchange reaction; subsequent coupling of a carbonyl group with [13C2]triethyl phosphonoacetate, followed by hydrogenation and hydrolysis, led to the stable labeled compound. Incorporation of two carbon‐13 atoms in the molecule eliminated the presence of undesired M+0.